Craftsmanship : GRAy magazine issue 2. - McNally, Clare; Gry, Lane; Kalmre, Risto (Amsterdam : Gerrit Rietveld Academie, 2006)
Archer, Elinor ; Wortel, Maartje ; Arpo, Eve ; Assman, Gijs ; van Baarsen, Suzanne ; Blaisse, Maria ; Brandt, Thyra ; Brown, Ian ; van den Dungen, Danny ; van Essen, Aaf ; Gangloff, Paul ; et al.
boek